Occupational attrition in professionals in the treatment area of women's prisons in Chorrillos - 2015 - Quispe Gutiérrez, Yovana (2016)
The objective of the investigation was to determine the differences in the levels of occupational burnout according to the institution of origin in workers in the treatment area of women’s prisons in the Chorrillos district. The research design was non-experimental transactional and descriptive-comparative type. The sample consisted of 93 workers, 33 of the Virgin of Fatima, 35 of the Women’s Penalty of Chorrillos and 25 of the Criminal Women of Chorrillos. For this, the Occupational Wear Scale (EDO) was administered. In addition, for reliability, the Cronbach’s alpha coefficient was used. The results show that 54% of the workers in the treatment area of women’s prisons in the district of Chorrillos have a level above the average of occupational burnout, which is also evident in the dimensions. Testing of the hypotheses was tested using the analysis of variance (test F), since the T scores come from normalized data. The comparative results show that there are no significant differences in occupational burnout by institution of origin.